Sistem Informasi Data Guru MDTA/TPSA Serta Gharim dan Imam Mesjid Secara Online - Reti Handayani; Novia Lestari (Prosiding SISFOTEK, 2018)
MDTA as one of the places of non-formal education is often the location directly join the mosque environment, both facilities and teachers. Therefore, many teachers of MDTA or TPSA are directly double positions as well as Gharim or imam mosque. In addition, the semimanual data recording for teachers of MDTA, gharin mosque, and imam of the mosque, makes it difficult for the District Welfare Department to record the teachers of MDTA, mosque gharin, and mosque imams who deserve annual assistance in accordance with the criteria set by the government, dual positions and must be active in the duties and positions both as a teacher MDTA, gharin mosque, and imam mosque at least 1 year of service. With the advancement of existing information technology, it is necessary to build a data information system of teachers of MDTA / TPSA, gharim and mosque faith online, which can facilitate in the recording and accelerate reporting data MDTA / TPSA, gharim and faith mosque one of them to be able to obtain annual assistance.